Avaliação da composição fitoquímica, da atividade antioxidante e da toxicidade in vivo de Leandra australis - Fortes, Thainara de Andrade (2021)
The richness of Brazilian biodiversity and the popular tradition of plants known as medicinal make phytotherapy widely used today. Among the plants used, the species Leandra australis, popularly known as pixirica, stands out. This species is popularly used for inflammatory diseases and as a weight-loss. Despite its popular uses, there are few studies in the current literature on its chemical molecules and pharmacological activities. Furthermore, so far, no toxicological studies have been found with this plant species. Therefore, this work aimed to evaluate the chemical composition, toxicity and antioxidant activity of L. australis. The plant was collected in March/2015, identified and extracted by maceration, with etanol 50%. Subsequently, its crude extract was fractionated with increasing polarity solvents (hexane, chloroform, ethyl acetate and butanol). The crude extract, fractions and remaining aqueous residue of the fractionation were concentrated in a rotary evaporator at a temperature below 45°C. The evaluation of the chemical composition by High Performance Liquid Chromatograph (HPLC) coupled to Mass Spectrometry was performed with the crude extract. Quantifications of secondary metabolites (total polyphenols, flavonoids, condensed tannins and total alkaloids) were performed in Spectrophotometry UV-Vis with the crude extract, fractions and aqueous residue. The evaluation of the antioxidant activity of the extract, fractions and aqueous residue was carried out by three different methods also carried out in Spectrophotometer UV-Vis, namely: evaluation of DPPH radical capture, determination of iron reduction ability (FRAP), and co-oxidation with beta-carotene and linolenic acid. The evaluation of the toxicity of the crude extract was carried out using alternative methods in vivo, being the cytotoxicity carried out on Artemia salina and the genotoxicity carried out on Allium cepa radicle cells. Toxicity was also assessed from the OECD 423 and 407 acute toxicity and repeated dose 28-day protocols using Wistar rats. The samples with the highest yield were aqueous residue, butanol and crude extract. In the assays, the high content of phenolic compounds and condensed tannins in the samples stood out, being also possible to quantify the gallic acid (19.32±0.39 mg/g of extract), rutin (12.30±0.01 mg/ g of extract) and quercetin (162.58 ± 0.68 mg/g of extract) in the plant extract analyzed in HPLC. The species under study showed considerable antioxidant activity in its extract and fractions. The toxicity profile of the species, unprecedented, did not show cytotoxicity to A. salina (LC50 1607.15 μg/mL), but a possible antiproliferative (genotoxic) activity in the crude extract of this species was evidenced. The evaluation of toxicity in Wistar rats showed that the acute administration and repeated doses did not cause deaths or behavioral changes in the animals. However, acute administration identified changes in BUN levels in the animals tested, which shows possible kidney damage. When administered continuously for 28 days, the plant did not cause hematological changes and the biochemical evaluation did not identify signs of toxicity. These results show that the plant species has low toxicity and reinforces the importance of conducting studies on chronic oral administration in order to confirm its safety for medicinal use.